Therapeutic Targeting of Neutrophil Granulocytes in Inflammatory Liver Disease - Bartneck, Matthias; Wang, Jing (Frontiers in Immunology, 2019)
Neutrophil granulocytes are the most numerous type of leukocyte in humans bearing an enormous, yet largely unexplored therapeutic potential. Scientists have very recently increased their efforts to study and understand these cells which contribute to various types of inflammatory diseases and cancer. The mechanisms that regulate neutrophil recruitment to inflamed tissues and neutrophil cytotoxic activities against host tissues and pathogens require more attention. The reactive oxygen species (ROS) are a popular source of cellular stress and organ injury, and are critically expressed by neutrophils. By combating pathogens using molecular combat factors such as neutrophil extracellular traps (NETs), these are immobilized and killed i.e. by ROS. NETs and ROS are essential for the immune defense, but upon excessive activation, may also harm healthy tissue. Thus, exploring new routes for modulating their migration and activation is highly desired for creating novel anti-inflammatory treatment options. Leukocyte transmigration represents a key process for inflammatory cell infiltration to injury sites. In this review, we briefly summarize the differentiation and roles of neutrophils, with a spotlight on intravital imaging. We further discuss the potential of nanomedicines, i.e. selectin mimetics to target cell migration and influence liver disease outcome in animal models. Novel perspectives further arise from formulations of the wide array of options of small non-coding RNA such as small interfering RNA (siRNA) and micro-RNA (miR) which exhibit enzymatic functions: while siRNA binds and degrades a single mRNA based on full complementarity of binding, miR can up and down-regulate multiple targets in gene transcription and translation, mediated by partial complementarity of binding. Notably, miR is known to regulate at least 60% of the protein-coding genes and thus includes a potent strategy for a large number of targets in neutrophils. Nanomedicines can combine properties of different drugs in a single formulation, i.e. combining surface functionalization with ligands and drug delivery. Inevitably, nanomedicines accumulate in other phagocytes, a fact that should be controlled for every novel formulation to restrain activation of macrophages or modifications of the immunological synapse. Controlled drug release enabled by nanotechnological delivery systems may advance the options of modulating neutrophil activation and migration.